Pengaruh Performance Appraisal terhadap Motivasi Kerja PNS Sekretaris Daerah Kabupaten Abdya - Novita , Erna; Rusdi, Rusdi (Regress: Journal of Economics & Management, 2022)
Performance appraisal is something that is no doubt very necessary and in some theories it turns out to have close connectivity with motivation. In the conventional performance appraisal process, civil servants often feel that their performance is not being paid attention to and this will certainly reduce their level of ability to compete and excel. This study aims to see how attached the performance appraisal process is to the motivation of civil servants in maintaining their performance and theoretically form a new horizon regarding the performance appraisal process itself. This research is located at the Regional Secretariat office of Southwest Aceh District and was conducted for 3 weeks in October and November 2022. This research involved 84 respondents, all of whom were civil servants. The results of the study show that performance appraisal is necessary to increase work motivation